2022
DOI: 10.1186/s43054-022-00123-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severe childhood community-acquired pneumonia: a retrospective study from two hospitals

Abstract: Background Community-acquired pneumonia (CAP) is the leading cause of death in children globally. Indonesia is ranked 1st in South East Asia with the highest burden of pneumonia. Identification of risk factors is necessary for early intervention and better management. This study intended to describe CAP’s clinical signs and laboratory findings and explore the risk factors of severe CAP among children in Indonesia. Methods This was a retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Community-ac quired pneumonia is frequent among children, severe pneumonia, especially, a severe sickness with an abrupt start and progression endangering children's health. If not recognized and treated promptly, it is the primary cause of child mortality [1]. Pathogenic infections with high pathogenicity are the most common cause of severe community-acquired pneumonia (CAP).…”
Section: Introductionmentioning
confidence: 99%
“…Community-ac quired pneumonia is frequent among children, severe pneumonia, especially, a severe sickness with an abrupt start and progression endangering children's health. If not recognized and treated promptly, it is the primary cause of child mortality [1]. Pathogenic infections with high pathogenicity are the most common cause of severe community-acquired pneumonia (CAP).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Rudin et al,(6) found that about 7-13% of pneumonia cases progress to the severe form; however, the risk factors for progression to severe pneumonia are not well documented in Uganda. In low and middle income countries, documented risk factors for severe pneumonia encompass bacterial causes, immunization status, low weight-for-age, limited caregiver education, lower wealth quintile, delayed care-seeking, household overcrowding, comorbidities, malnutrition, and young age (7)(8)(9). However, these factors exhibited inconsistencies and variations, in uenced by unique contextual disparities across different settings.…”
Section: Introductionmentioning
confidence: 99%